Political Competitiveness and Voters Behaviour: An Exploratory Study - Munira, Abdul Razak; Muhammad Nubli, Abdul Wahab; Noradilah, Md Nordin (2015)
This study examined the causal relationship of political competitiveness and voters’ behaviour in Malaysia. Questionnaires were developed and distributed to 14 focus groups which involved 760 respondents in the age of 21-60 years old. The data collected from a longitudinal study was analysed using Atlas.ti and SPSS 22; that generates graphic Network and descriptive statistical analysis to analyse the theory. From the result it can be found that both the political competitiveness and the voters’ behaviour are influenced by the integrated delivery system. This finding signifies the way of empowering integrated delivery system and to enhance the political competitiveness quality in Malaysia.